Genetics of domestication and world-wide introduction of Bos indicus (Zebu) and Bos taurus (Taurine) cattle - KUMAR, SUSHIL; KUMARI, RENU; SHARMA, VISHAKHA; YADAV, M P (The Indian Journal of Animal Sciences, 2016)
Neolithic people who had already domesticated crops such as barley and wheat, domesticated cattle more than 8,500 years ago. This development transitioned human populations from hunter-gatherers to sedentary complex societies. Modern cattle comprise mainly of two species (or types) Bos taurus (taurine) and Bos indicus (zebu or Indicine) which are distributed world-wide; and some minor species of cattle, including Bos grunniens (yak), Bos frontalis (gayal/mithun) and Bos javanicus domesticus (Bali banteng) are also important in East and Southeast Asia. Neolithic period onwards cattle have been deployed to plough land for efficient agriculture; yield milk, meat and leather and for making yoghurt, cheese and ghee from milk; transport people and goods in carts. Historical accounts of 10000 years and archaeological findings of Neolithic period have been complemented by recent mitochondrial and nuclear genetical-genomical evidences to understand the pre- and post- domesticated history of cattle. Analyses of nuclear and mitochondrial genome sequences for polymorphism at DNA markers in ancient (extinct) and modern cattle has revealed the parentage of cattle species, approximate dates and places of their domestication, approximate dates and routes of their migration to new habitats on different continents, and times and places of introgression from wild aurochs in Europe and Africa and admixture between species. Cattle have undergone natural and strong artificial selection for adaptation to varied environments, fertility, social behaviour, milk and meat yields, milk quality and aesthetic morphological features which have had pronounced effect on cattle genome, causing reduction in genetic variability. Here a brief review is presented about genetical evidence on above aspects and future research directions are also identified.